Releitura contemporânea do crime de concorrência desleal: uma análise jurídica e a necessidade de reforma penal - Gonçalves, Aline Martins (2024)
The present master's thesis investigates the conducts that constitute the crime of unfair competition, as delineated in the fourteen clauses of Article 195 of the Industrial Property Law (Law N. 9.279/1996), highlighting the subsequent need to improve related legislative provisions and update the corresponding penal type. In summary, unfair competition criminalizes the behavior of market agents who, having a duty of probity in market competition, deliberately cause harm to competitors by breaching this duty. From a penal perspective, distinct actions with identical legal consequences are explored, highlighting the insufficient penal protection. Critiques of the positive penal model relate to the extensive infractions chosen by the legislator, which, despite differing in severity, are uniformly sanctioned, all being punished in a straightforward manner. The study begins with the presentation of concrete cases currently discussed in doctrine and jurisprudence, addressing the classification of these situations within the categories outlined as crimes of unfair competition. It then proceeds to a detailed analysis of the conducts described and the legal goods protected by Article 195 of the Industrial Property Law. Next, it is shown that the legislation is not limited to the exclusive protection of industrial property, but also covers other essential elements of the business, expanding the understanding of legal protection beyond the strict limits of industrial property. After addressing these points, the thesis criticizes the Brazilian penal system in the context of unfair competition, highlighting the lack of proportionality in penalties and the need for reform. It concludes by emphasizing the urgency of restructuring the penal type for better protection of competitors and to ensure a more effective and coherent judicial system.